(a)

Let \(\displaystyle\alpha={a}+{b}{i}\ \text{ and }\ \beta={c}+{d}{i}\)

\(\displaystyle\overline{{\alpha+\beta}}=\overline{{{\left({a}+{b}{i}\right)}+{\left({c}+{d}{i}\right)}}}\)

\(\displaystyle=\overline{{{\left({a}+{c}\right)}+{i}{\left({b}+{d}\right)}}}\)

\(\displaystyle={\left({a}+{c}\right)}-{i}{\left({b}+{d}\right)}\)

\(\displaystyle={a}+{c}-{i}{b}-{i}{d}\)

\(\displaystyle={\left({a}-{i}{b}\right)}+{\left({c}-{i}{d}\right)}\)

\(\displaystyle=\overline{{\alpha}}+\overline{{\beta}}\)

Similarly,

\(\displaystyle\overline{{\alpha\beta}}=\overline{{{\left({a}+{b}{i}\right)}{\left({c}+{d}{i}\right)}}}\)

\(\displaystyle=\overline{{{a}{c}-{b}{d}+{i}{\left({b}{c}+{a}{d}\right)}}}\)

\(\displaystyle={a}{c}-{b}{d}-{i}{\left({b}{c}+{a}{d}\right)}\)

\(\displaystyle={\left({a}-{i}{b}\right)}{\left({c}-{i}{d}\right)}\)

\(\displaystyle=\overline{{\alpha}}\overline{{\beta}}\)

Thus, \(\displaystyle\overline{{\alpha+\beta}}=\overline{{\alpha}}+\overline{{\beta}}\ \text{ and }\ \overline{{\alpha\beta}}=\overline{{\alpha}}\overline{{\beta}}\)

Step 2

(b)

Let A nad B are the matrices whose entries are from complex numbers. (i,j)th entry of AB is \(\displaystyle{a}_{{{i}{1}}}{b}_{{{1}{j}}}+{a}_{{{i}{2}}}{b}_{{{2}{j}}}+\dot{{s}}+{a}_{{\in}}{b}_{{{n}{j}}}\)

From part (a),

\(\displaystyle\overline{{{a}_{{{i}{1}}}{b}_{{{1}{j}}}+{a}_{{{i}{2}}}{b}_{{{2}{j}}}+\dot{{s}}+{a}_{{\in}}{b}_{{{n}{j}}}}}=\overline{{{a}_{{{i}{1}}}{b}_{{{1}{j}}}}}+\overline{{{a}_{{{i}{2}}}{b}_{{{2}{j}}}}}+\dot{{s}}+\overline{{{a}_{{\in}}{b}_{{{n}{j}}}}}\)

\(\displaystyle=\overline{{{a}_{{{i}{1}}}}}\overline{{{b}_{{{1}{j}}}}}+\overline{{{a}_{{{i}{2}}}}}\overline{{{b}_{{{2}{j}}}}}+\dot{{s}}+\overline{{{a}_{{\in}}}}\overline{{{b}_{{{n}{j}}}}}\)

This implies that i,j) th entry of \(\displaystyle\overline{{{A}{B}}}\ \text{ and }\ \overline{{{A}}}\overline{{{B}}}\) are same.

It is known that if each of entry of two matrices are same then they are equal.

Hence, \(\displaystyle\overline{{{A}{B}}}=\overline{{{A}}}\overline{{{B}}}\)